Assessment of maternal factors and fetomaternal outcome in pregnant women conceived by artificial reproductive techniques - Jatav, Deepika; Chandwaskar, Nootan; Arya, Madhuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Infertility is a major issue and a source of social and psychological suffering for many couples. Introduction of assisted reproductive technology (ART) leads to great relief for couples nowadays. Methods: This present observational cross-sectional study was conducted at OBGY Department at Sri Aurobindo Medical College and Post Graduate Institute, Indore and who satisfy the inclusion criteria was studied from 1st April 2021 to 30th September 2022 (18 months). After approval from Institutional ethical committee. Each patient fulfilling the inclusion criteria was included in the study. Informed written consent was taken. Results: The mean age of women in this study was 37.6 years and the most common age group was between 30-50 years. Infertility was mostly unexplained (40%), followed by female factor (33.33%), male factor (16.67%), and combined (10%). 63.33% were singletons, 36.67% twins. Preterm labor (43.33%) was most common. Preeclampsia/eclampsia (33.33%), gestational hypertension, renal failure, gestational diabetes, cardiomyopathy, hepatic failure, HELLP syndrome, and DIC were other complications. 60% were caesarean-sectioned and 40% vaginal delivery. 90.24% of neonates had 5-minute Apgar scores above 7 and 9.76% below 7. 4 stillbirths (9.76%) and 75.68% of live births required NICU admission. 5 neonatal deaths (12.2%) and 21.95% perinatal mortality. Conclusions: There are numerous maternal and perinatal complications linked to ART. Couples should therefore be counselled about these risks while offering them ART as a mode of conception.